Problems in the Creation of Authentic Deeds by Notaries: Formal Truth and Material Truth - Sandrarina Hertanto; Tjempaka Tjempaka (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2026)
Authentic deeds have full evidentiary force, making notaries public officials who provide legal certainty to the parties. However, the establishment of truth in authentic deeds creates uncertainty between formal truth and material truth, which in reality often leads to a broader understanding of the role of notaries. The purpose of this study is to critically evaluate the conceptualization of formal truth and material truth through the lens of evidence theory, as well as to investigate the normative limits of notary authority based on Law No. 2 of 2014. This is a normative legal study with a legislative and intellectual focus. The results of the study show that the evidentiary value of authentic deeds is inherently based on formal truth, namely the conformity between the parties' statements and their recording in the deed by the notary in accordance with the applicable legal process. Meanwhile, material truth regarding the substance of legal facts is limited to the evidence submitted by the parties and the judicial system. Thus, the appointment of notaries as guarantors of material truth violates both evidence theory and professional standards. This essay emphasizes the need for a clear conceptual separation between formal truth and material truth in order to avoid distortion of notarial authority and maintain the consistency of the evidence system in civil law.